Management model of financial potential of the production enterprise - Maslуhan, О.; Kulinich, T.; Zhadanova, Yu.; Biletska, N.; Buhaiova, M. (Kuprienko SV, 2022)
Монографія містить наукові дослідження авторів. Може бути корисна для керівників, інженерів, юристів, економістів та інших працівників підприємств і організацій, а також викладачів, здобувачів, аспірантів, магістрантів і студентів вищих навчальних закладів. The monograph contains scientific studies of authors. It may be useful for managers, engineers, lawyers, economists and others employees of enterprises and organizations, as well as teachers, applicants, graduate students, undergraduates and students of higher educational institutions.
Keywords: наукові дослідження; модель управління; фінансовий потенціал; підприємство; сегментація; scientific research; management model; financial potential; enterprise; segmentation; 001.895; DOI: 10.30888/2663-5569.2022-22-01